Radio as a tool of propaganda in Nazi Germany - Janowska, Aleksandra (Migracja w języku, literaturze i kulturze, 2020)
Those whose interests are closely focused on the history of Germany, would find the term of Nazi propaganda exceptionally interesting. This is, in particular, when focusing on the history of the Third Reich. This case is directly correlated to the Minister of Propaganda and Public Enlightenment – Joseph Goebbels, who, before the Second World War, used the so-called Volksempfänger (people’s receiver) in order to spread the Nazi propaganda. At the outbreak of the World War II, 70% of the citizens of the Third Reich had radio receivers in their homes. Military marches and Hitler’s speeches were, as a matter of fact, the only means of entertainment provided to the listeners. Anything that was in the service of propaganda, could be heard on the radio – other kinds of broadcasts were strictly prohibited. After war, radio became a reappearing motif in the movies, books and music. Jacob der Lügner ( Jacob the Liar,) a novel written by Jurek Becker, makes for a relevant example of such a case. The main character of the story, uses radio communication as a tool to help other Jews in the ghetto believe that they may soon regain freedom. Even though in case of both – Nazi Germany and the aforementioned work, the radio was used as a manipulation tool, its concluding manifestation was different. In Goebbels’s case, manipulation was closely related to propaganda, whereas in Becker’s novel, it was supposed to give a false hope for a better tomorrow.